Whole Exome Sequencing Study of Parkinson Disease and Related Endophenotypes in the Italian Population - Gialluisi, Alessandro; Reccia, Mafalda Giovanna; Tirozzi, Alfonsina; Nutile, Teresa; Lombardi, Alessia; De Sanctis, Claudia; , International Parkinson's Disease Genomic Consortium (IPDGC); Varanese, Sara; Pietracupa, Sara; Modugno, Nicola; Simeone, Antonio; Ciullo, Marina; et al. (Frontiers in Neurology, 2020)
Parkinson Disease (PD) is a complex neurodegenerative disorder characterized by large genetic heterogeneity and missing heritability. Since the genetic background of PD can partly vary among ethnicities and neurological scales have been scarcely investigated in a PD setting, we performed an exploratory Whole Exome Sequencing (WES) analysis of 123 PD patients from mainland Italy, investigating scales assessing motor (UPDRS), cognitive (MoCA) and other non-motor symptoms (NMS). We performed variant prioritization, followed by targeted association testing of prioritized variants in 446 PD cases and 211 controls. Then we ran Exome-Wide Association Scans (EWAS) within sequenced PD cases (N=113), testing both motor and non-motor PD endophenotypes, as well as their associations with Polygenic Risk Scores (PRS) influencing brain subcortical volumes. We identified a variant associated with PD, rs201330591 in GTF2H2 (5q13; alternative T allele: OR[CI] = 8.16[1.08; 61.52], FDR = 0.048), which was not replicated in an independent cohort of European ancestry (1,148 PD cases, 503 controls). In the EWAS, polygenic analyses revealed statistically significant multivariable associations of amygdala- (β(SE) = -0.039(0.013); FDR = 0.039) and caudate-PRS (0.043(0.013); 0.028) with motor symptoms. All subcortical PRSs in a multivariable model notably increased the variance explained in motor (adjusted-R2=38.6%), cognitive (32.2%) and other non-motor symptoms (28.9%), compared to baseline models (~20%). Although the small sample size warrants further replications, these findings suggest shared genetic architecture between PD symptoms and subcortical structures, and provide interesting clues on PD genetic and neuroimaging features.